Investigation of DNAPL migration in double-porosity media using image analysis - Lim, Chia Ni (2016)
Nowadays, non-aqueous phase liquids (NAPL) are one of the common contaminants that lead to soil pollution. In this study, laboratory experiments were carried out to investigate the dense non-aqueous phase liquid (DNAPL) migration in double-porosity media using light transmission visualization (LTV) method. Two experiments were conducted in different types of double-porous media; namely aggregated kaolin with moisture content of 30% as well as a mixture of sintered clay spheres and Ottawa sand. An experimental setup was specially designed to execute the LTV method. Dyed tetrachloroethylene (PCE) which is one of the DNAPLs was poured into both experiments in order to study the behavior of DNAPL migration. The instantaneous migration of PCE in the double-porosity media was captured by a digital camera. Image analysis was applied to all the captured images. Experimental results obtained from the image analysis were discussed qualitatively in terms of area, vertical distance travelled, velocity and saturation. Besides, the comparison was made between the pouring method and injection method of PCE in 30% moisture content of aggregated kaolin sample. Regarding to the obtained results from different release methods of PCE, the coverage of PCE was larger under pouring method. Furthermore, for the experiment of a mixture of sintered clay spheres and Ottawa sand, PCE migration ceased at the half height of test sample due to the absorbability of sintered clay spheres only. This phenomenon was credited to Ottawa sand has no effect to the absorption of water and air. Hence, coverage of PCE in aggregated kaolin test sample was bigger than the mixture of sintered clay spheres and Ottawa sand. It was found that different release methods of PCE and the types of double-porosity soil media can become the influential factors in PCE migration.